Conduction Block in PMP22 Deficiency - Bai, Yunhong (Society for Neuroscience, 2010)
Patients with PMP22 deficiency present with focal sensory and motor deficits when peripheral nerves are stressed by mechanical force. It has been hypothesized that these focal deficits are due to mechanically induced conduction block (CB). To test this hypothesis, we induced 60–70% CB (defined by electrophysiological criteria) by nerve compression in an authentic mouse model of hereditary neuropathy with liability to pressure palsies (HNPP) with an inactivation of one of the two pmp22 alleles (pmp22(+/−)). Induction time for the CB was significantly shorter in pmp22(+/−) mice than that in pmp22(+/+) mice. This shortened induction was also found in myelin-associated glycoprotein knock-out mice, but not in the mice with deficiency of myelin protein zero, a major structural protein of compact myelin. Pmp22(+/−) nerves showed intact tomacula with no segmental demyelination in both noncompressed and compressed conditions, normal molecular architecture, and normal concentration of voltage-gated sodium channels by [(3)H]-saxitoxin binding assay. However, focal constrictions were observed in the axonal segments enclosed by tomacula, a pathological hallmark of HNPP. The constricted axons increase axial resistance to action potential propagation, which may hasten the induction of CB in Pmp22 deficiency. Together, these results demonstrate that a function of Pmp22 is to protect the nerve from mechanical injury.